Desain dan Penerapan Website Pemesanan Undangan Digital dengan Integrasi Layanan WhatsApp di WeddingKu Design - Awan Eka Dana; Farelli Faith Andriyanto; Mutiara Mutiara; Raina Oktavia; Warda Agil Putri Kristiana (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to design and develop a website-based digital invitation ordering information system that is integrated with WhatsApp services. This system was developed as a solution to the need for efficiency in the process of ordering and distributing invitations that are environmentally friendly. The system design uses the Unified Modeling Language (UML) approach to visualize the overall system requirements. The main features developed include invitation ordering, design catalog selection, user and admin account management, and automatic notification via WhatsApp. This system is expected to increase the effectiveness and efficiency in managing orders by the admin, as well as provide convenience for customers in placing orders quickly, accurately, and flexibly. The test results show that this system can run well and meet user needs. With this system, the process of ordering and distributing invitations becomes more practical, modern, and in accordance with the development of digital technology today.